Gender Dimension of Migration from Central Asia to the Russian Federation - Anna Rocheva; Evgeni Varshaver (Asia-Pacific Population Journal, 2018)
The article considers the relationship between migration from Central Asia to the Russian Federation and gender relations. In particular, the paper describes the age-sex composition of the migration flows from three countries of the subregion (Kyrgyzstan, Uzbekistan, Tajikistan) and discusses the case of Kyrgyzstan with its active female migration. Male migrants are more often employed in construction and are paid more than female migrants, who work mostly in trade and services. However, men and women show almost no difference in complying with migration laws, vulnerability in interactions with the state, relations with employers and apartment owners as well as transnational practices. The article also considers possibilities for family reunification, and gendered differences in inter-ethnic communication. The article concludes that further studies are required, and that assistance mechanisms are required for women who do not receive financial assistance from their migrant husbands. The article also finds that migrants’ sexual and reproductive behaviour is characterized by limited access to information about risks and also requires thorough study.